Parenting behaviors of mothers of Croatian adolescents: Sociodemographic predictors - Brković, Irma (Array, 2007)
Parenting practices have traditionally been studied as antecedents of various outcomes in children. On the other hand, Belsky developed the process model of determinants of parenting aiming at understanding the factors that cause interindividual differences in parenting behaviors. He especially highlighted the social-contextual factors that shape parenting and that, among others, include attributes of children and social context in which parenting is embedded. In present research we investigated the extent to which mothers´ parenting behavior can be explained by child´s (age and gender) and mother´s (age and education) socio-demographic characteristics, and characteristics of the family (income and number of children). The sample consisted of 812 mothers and their adolescent children (both girls and boys) from twoparent Croatian families. Mean maternal age was 39.5 years and children attended 5th to 8th grade. Parenting behaviors were assessed by self-ratings on Croatian Parental Behavior Questionnaire (Kerestes, Kuterovac Jagodic & Brkovic, 2006). Significant predictors of Positive parenting were child´s age and gender - mothers expressed more positive parenting behaviors toward younger children and towards girls. Family income was also positively correlated with positive parenting. Negative parenting was predicted by mother´s education - less educated mothers expressed more negative parenting -and by child´s gender - mothers expressed more negative parenting toward boys. Less educated mothers were more permissive toward their children. Furthermore, in families with more children mothers were less permissive. Mother´s age was not significant predictor for any dimension of parenting. Investigated variables had limited predictive validity in the context of determinants of parenting.